Purification of Flavone C-Glycosides from Bamboo Leaves by Macroporous Adsorption Resin - Guo, Hui; Fan, Kang-Mei; Qian, Jun-Qing (Asian Journal of Chemistry, 2014)
A simple and efficient process for purification flavone C-glycosides from bamboo leaves was developed in this paper. The adsorptive properties of flavone C-glycosides on the resins were evaluated. Among the ten macroporous resin adsorbents tested, the non-polar resin H103 has the best adsorption and desorption performance. Besides, the static equilibrium adsorption data fitted well with the Langmuir equation. The gradient elution program was as follows: 2 BV (bed volume) of deionized water, 2 BV of 20 % ethanol, 5 BV of 80 % ethanol at a flow rate of 1 mL/min. After the H103 resin treatment, the contents of the total 6 flavone C-glycosides were increased from 2.49 to 50.40 %, the recovery rate of which was 69.73 %. Therefore, the method can be applied to the separation of flavone C-glycosides from bamboo leaves.